Molecular Dynamics Calculations of CH3 Sticking Coefficient onto Diamond Surfaces. Issue 8 (24th February 2015) - Schwaederlé, Laurent; Brault, Pascal; Rond, Cathy; Gicquel, Alix
<x xml:space="preserve">Abstract</x> A molecular dynamics model is implemented in a way dedicated to simulate initial conditions close to microwave plasma deposition of thick single crystal diamond films. The sticking coefficient of CH3 radical is obtained for (111) and (100) surface at three gas and substrate temperatures: 1 120, 1 200, and 1 500 K. A low value of 5.10−4 is obtained, which is consistent with experimental findings claiming values less than 0.01 or equating to 8.10−3 at 1 120 K.<inline-graphic xlink:href="ark:/27927/pgj2dsjg8pg" content-type="ppap201400223-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />